Adrián Muñoz, Radiografía del Hathayoga, México, El Colegio de México, 2016, 354 pp. - García Fernández, Roberto Eduardo (El Colegio de México, 2017)
Adrián Muñoz, Radiografía del Hathayoga, México, El Colegio de México, 2016, 354 pp.